The Influence of Teacher Role Models, Student Religious Motivation, and Islamic Spiritual Activities on Student Religiousness Levels - Suhartini, Andewi; Ratnasih, Teti; Purnama Sari, Yuni; Arrofi, Muhammad Raid; Rosita, Nia (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
This study is in the discourse of Islamic education and religious psychology, focusing on factors that influence the internalization of religious values in the madrasah environment. The main objective of this article is to analyze and test the partial and simultaneous effects of Teacher Role Models (X1), Student Religious Motivation (X2), and Islamic Spiritual Activities (X3) on Student Religiousness Levels (Y) at MAN 1 Bandung Regency. The research method used was a quantitative approach with multiple regression analysis techniques. Data were collected through questionnaires distributed to a sample of 207 eleventh-grade students. Based on the testing, the three independent variables were partially proven to have a positive and significant influence on the Level of Religiosity (Teacher Role Models Sig.=0.002; Religious Motivation Sig.=0.000; Islamic Spiritual Activities Sig.=0.000). Simultaneously, Teacher Exemplarity, Religious Motivation, and Islamic Spiritual Activities contributed 63.8% to the dependent variable (Sig. = 0.000). The most prominent research finding is that Student Religious Motivation is the most dominant predictor with the highest standardized Beta value (beta = 0.525), indicating that the students' internal spiritual motivation is stronger than the influence of teachers or school programs. This paper contributes to confirming theories of religiosity while also contributing a perspective of influence hierarchy, emphasizing that madrasah strategies must focus on strengthening students' spiritual motivation. The results of this study are important as a basis for formulating madrasah policies that shift the focus from merely delivering material to building intrinsic religious awareness.